ECOLOGICAL FACTOR SCORE OF THE TOBACCO CULTIVATION ON THE ENVIRONMENT - Архіпова, Г.; Макаренко, Ю. (Proceedings of National Aviation University (archive), 2012)
The problem of the quality and safety of tobacco cultivation in Ukraine was described in the article. Asfar as the cultivation of this plant is accompanied by using of the pesticides and other hazardous chemicals,the problem requires the solution in the nearest future. The techniques of "organic" tobacco cultivation,which are used in other countries and can be adopted in Ukraine, have been considered